Development of basic ways to implement predictive scenarios of economic development of the Republic of Belarus on the basis of a modified model of inter-industrial ba lance - Korotkevich, Aleksei I. (Journal of the Belarusian State University. Economics, 2018)
Address issues for basic implementation options predictive scenarios of economic development of the Republic of Belarus on the basis of a modified model of inter-industrial balance. The Basic objects are forecasting and planning economic activities. The main planned parameters: output products; number of resources, including labour force; profit; price resources, including wages; volumes and prices of the final, final and intermediate products; accumulation and consumption; movement of national wealth, imports and exports.